Design of a Classroom Noise Monitoring Tool Using a KY-037 Sound Sensor Based on Wemos D1R1 - Rifqah, Raden Ayu Nurfadhillah; Suciyati, Sri Wahyu; Surtono, Arif; Pauzi, Gurum Ahmad (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
The noise level in the room is one of the factors that can influence teaching and learning activities. Research on classroom noise levels has been done using the Wemos D1 R1-based KY-037 sound sensor. This research aims to determine the noise level in the classroom and be able to monitor the noise level in the room. Data collection was carried out by sound detection in the classrooms of SMA Negeri 13 Palembang from 07.00 – 12.00 WIB for seven days. The research results show that the system is functioning well, indicated by the situation when the noise level is less than 45 dB, and the LED lights up. When the noise level is more than or equal to 45 dB, then the yellow LED, mini DFPlayer, and speaker will light up, and when the noise level is more than or equal to 55 dB, then the red USB LED, mini DFPlayer, and speaker will light up. Data on noise levels and LED conditions received can be monitored via the web server. The system used on the web server is localhost access on a computer that can be monitored within the school environment.